(untitled) (Carte Romanze, 2020)
The so-called cantiga da guarvaia has been copied in the Cancioneiro da Ajuda with some scribal errors that affect the metrical structure of the poem. In recent years two different hypothesis connected the cantiga to an Occitan model, and have affected the way the text has been edited. This article tries to establish which Occitan text has been imitated by Pay Soarez de Taveirós and analyses the way the text has been amended by the editors.